[Breaking up is hard ; A question of arms ; Anything is possible [videorecording] - Lazaro, Cheche (The Probe Team ; [episode no.160], 1991)
Looks into the alternatives to the bases of the U.S. announced pull-out from Clark; issues on gunless society; and an interview with Debbie Gibson a teeny bopper sensation in the U.S.